Handbook of the London 2012 Olympic and Paralympic games volume one : making the games - Girginov, Vassil (Routledge handbooks, 2013)
The Handbook of the London 2012 Olympic and Paralympic Games is an authoritative and comprehensive account of the world's greatest sporting and cultural event. It tells the complete story of the 2012 Games from inception, through the successful bidding process and the planning and preparation phase, to delivery, the post-Games period and legacy. Written by a world-class team of international Olympic scholars, the book offers analysis of the full social, cultural, political, historical, economic and sporting context of the Games. From the political, commercial and structural complexities of organising an event on such a scale, to the sporting action that holds the attention of the world, this book illuminates every aspect of the 2012 Games, helping us to better understand the vital role that sport and culture play in contemporary global society.